Careers in multinational enterprises - Marcus Roesch; Michiel Gerritse; Bas Karreman (Tinbergen Institute, 2024)
Do workers in multinational enterprises (MNEs) build stronger CVs? We track the careers of all workers entering the Dutch labor market over the years 2006-2021 and find large and portable wage premia of MNE employment experience. Workers with experience at MNEs instead of domestic firms earn up to 14% higher wages within the MNE, and up to 11% higher wages after moving to another firm. Consistent with a model of MNEs that leverage the value of their employment experience, we find that MNEs hire more juniors, pay lower starting wages, and are more selective towards senior workers than domestic firms.
Keywords: F23; F66; J24; J31; 330; multinationals; experience wage premia; firm organization; AKM; knowledge spillovers; Netherlands